Behavioural analysis of customer involvement in innovative green supply chain management - MS. B. NEERAJA; MR. KARAN. V. K (The journal of contemporary issues in business and government, 2020)
The part of clients in the green supply chain, the board should be distinguished and perceived as a significant research zone. This paper is an endeavour to investigate the contribution part of clients towards the Green Supply Chain (SC). An observational exploration approach has been utilized to gather essential information to rank various factors for successful client association in green idea usage in Supply Chain. Relevant connections among factors have been built up utilizing specialists’ suppositions. The exploration may help rehearsing directors to comprehend the communication among factors influencing client contribution. Further, this comprehension might be useful in encircling the approaches and procedures to green Supply Chain. Examining connection among factors for powerful client association in GSCM to build up the basic model in the Indian point of view is an exertion towards advancing condition cognizance.